Alat Monitoring Kualitas Air Minum Menggunakan Sensor TDS Berbasis Internet of Things - Rouhillah; Rizki Faulianur; Fira Fazila (Politeknik Aceh, 2023)
Water is a natural resource that is very important for life, especially for humans. Human needs for clean water always increase from years to years. Mineral water from the depot makes it easier for consumers to choose the quality of mineral water. This final project aims to make a drinking water quality monitoring tool with a Total Dissolved Solid (TDS) sensor that can read dissolved substances in water. The microcontroller used to store sensor data is a NodeMCU ESP8266, the data is sent to Firebase then the data in Firebase will be forwarded to Android with Internet of Thing (IoT) technology. The result of the average error percentage for the comparison of the TDS sensor with the TDS meter is 16.82%. All test results from five samples of TDS sensor data and TDS meter can be concluded that the quality of drinking water is very good, because the sensor readings are below 300 PPM.